EVALUASI PENGGUNAAN PESTISIDA PADA PETANI BAWANG MERAH DI DESA WOMBO MPANAU KECAMATAN TANANTOVEA KABUPATEN DONGGALA - Tri Satyani; Arfan Arfan; Sayani Sayani (FAKULTAS PERTANIAN UNIVERSITAS ALKHAIRAAT, 2019)
This study aims to study and determine the behavior of farmers in the use of pesticides on shallots in Wombo Mpanau Village, Tanantovea District. This study uses a simple random method. The data obtained is collected, processed and analyzed. Analysis was carried out to determine the frequency of data in each variable. Primary data obtained through interviews were analyzed to provide a concise picture of groups of data in one frequency table. Types of pests that attack onion in Wombo Mpanau Village are leaf caterpillars, leaf flies, trips, flour dew, and fusarium wilt. The most widely used pest control method is the use of chemical pesticides, which reaches 70% of respondents. The knowledge of farmers on the application of pesticides is relatively good, namely 100% of respondents apply pesticides when there are symptoms of attack and if other controls are unable to overcome the pest attack. Knowledge of farmers on the use of doses of pesticides is relatively good, namely 100% of respondents use the dosage according to the recommendations listed on the packaging. The actions of farmers when applying pesticides in general are not mixing pesticides. The majority of respondents have taken the right action in terms of storing semrot and pesticides in a special place. But on the other hand the awareness of farmers is still low, because there are still many farmers who wash sprayers in rivers or ditches.